2018
DOI: 10.1186/s40478-018-0609-y
|View full text |Cite
|
Sign up to set email alerts
|

Satellite cells fail to contribute to muscle repair but are functional in Pompe disease (glycogenosis type II)

Abstract: Pompe disease, which is due to acid alpha-glucosidase deficiency, is characterized by skeletal muscle dysfunction attributed to the accumulation of glycogen-filled lysosomes and autophagic buildup. Despite the extensive tissue damages, a failure of satellite cell (SC) activation and lack of muscle regeneration have been reported in patients. However, the origin of this defective program is unknown. Additionally, whether these deficits occur gradually over the disease course is unclear. Using a longitudinal pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 96 publications
1
16
0
1
Order By: Relevance
“… 67 Similarly, a relatively slow rate of glycogen buildup in skeletal muscle of KO mice was demonstrated by us and others. 26 , 68 …”
Section: Discussionmentioning
confidence: 99%
“… 67 Similarly, a relatively slow rate of glycogen buildup in skeletal muscle of KO mice was demonstrated by us and others. 26 , 68 …”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of several caspases such as 1, 3, and 6 in skeletal muscle also suggests the activation of a degenerative/regenerative process, as reported in other forms of muscular dystrophy [65] . Recent studies reported that in PD mice the upregulation of genes associated with muscle regeneration is accompanied to a low number of regenerating myofibers due to reduced activation of muscle satellite cells [66] . Interestingly, in the present study transcriptomic analyses of Gaa KO skeletal muscle showed an important downregulation of Klotho , whose deficiency has been linked to impaired muscle regeneration due to defects in muscle progenitor cells [67] .…”
Section: Discussionmentioning
confidence: 99%
“…These data provided indirect evidence of a failure of satellite cell activation in Pompe disease. In the follow-up studies in murine models of Pompe disease, two independent groups [98,99] demonstrated that despite extensive muscle damage, the number of regenerating fibers in adult animals is essentially negligible. Remarkably, the satellite cells were fully functional and were able to robustly respond to acute and repeated muscle injury induced by cardiotoxin or barium chloride leading to efficient muscle regeneration comparable to that in WT controls.…”
Section: Beyond the Lysosome: Pathogenic Cascade And Muscle Regenerationmentioning
confidence: 99%